Effects of Polyethylene Terephthalate Fibre Reinforcement on Mechanical Properties of Concrete - NZ Nkomo; LM Masu; PK Nziu (Advances in Materials Science and Engineering)
Cracked concrete is a problem due to several factors such as poor maintenance, insufficient reinforcement, or steel corrosion leading to crack propagation. There is a need to increase the load-bearing capacity of concrete slabs and increase their life span. The use of waste polyethylene terephthalate fibres in concrete can dramatically alleviate the problem of crack propagation and failure sustainably. Furthermore, the utilization of waste plastic in this manner is environmentally friendly. This study presents the experimental investigation into the mechanical strength properties of concrete with respect to the effect of various mass fractions of polyethylene terephthalate fibre. The polyethylene terephthalate fibres were added at mass fraction of 0.5%, 1.0%, 1.5%, and 2.0%. An experimental investigation was carried out to explore the effect of varying fibre mass fractions on the slump value, rebound number, split tensile strength, flexural strength, and compressive strength. An increase in flexural strength, rebound number and compressive strength was noted with an increase in fibre mass fraction. However, a decrease in split tensile strength was noted. The addition of 0.5% fibre gave the highest compressive and flexural strength of 29.32 N/mm2 and 28 N/mm2, respectively. However, the addition of fibre lowered the split tensile strength beyond the control specimen at all fibre mass fractions. The experimental results of this study indicate that the addition of polyethylene terephthalate fibre enhances the mechanical strength of concrete at low fibre mass fraction percentages. The PET fibre reinforced concrete is suitable for use in paving and ceiling slabs at a fibre addition of 0.5% for optimum workability and mechanical strength.